Natural based reusable materials for microfluidic substrates: The silk road towards sustainable portable analytical systems. (August 2022) - Brito-Pereira, Ricardo; Macedo, André S.; Ribeiro, Clarisse; Cardoso, Vanessa F.; Lanceros-Méndez, Senentxu
Abstract: Portable analytical systems are versatile tools for application in areas including biomedicine, biosecurity, food safety and environmental monitoring. This work contributes to the increasing demand for low-cost, environmentally friendly substrates for portable analytical systems by using natural Bombyx mori cocoons. Further, silk fibroin is also extracted from these cocoons and electrospun into oriented and randomly oriented fiber substrates. Oxygen plasma treatment is applied to improve their hydrophilicity. Fiber morphology, mechanical properties, porosity, thermal characteristics and surface contact angle are extensively characterized and the ability of the samples for passive capillary flows demonstrated. Plasma treated pressed cocoons show superhydrophilicity, capillary flow rates of 44.8 ± 3.75 mm.min -1, and high mechanical resistance with Young's modulus values up to 592.13 ± 19.83 MPa. The developed materials are used as substrates for the colorimetric quantification of three commonly scrutinized clinical analytes. Hydrophobic barriers are first wax-printed on all samples with a proper design and albumin assays are performed on all substrates. Further assays for uric acid and glucose quantification are successfully accomplished on the pressed cocoons after a simple in between washing step, with overall high coefficient of determination, proving the suitability of the developed materials as low-cost, sustainable and reusable microfluidic substrates. Graphical abstract: Image, graphical abstract